An empirical study on coupling coordination between the cultural industry and tourism industry in ethnic minority areas - Zhaoxing Zhou; Qian Yang; Dong-Joo Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Background/Objectives: China is actively promoting the reform of its economic structure and industrial upgrade, and the integration of the cultural industry and the tourism industry is an important approach. It is necessary to explore the degree of coordination and coupling between the cultural industry and the tourism industry in ethnic minority areas and find ways to promote the coordinated development of the two industries. Methods/Statistical Analysis: This study selected Guangxi Zhuang Autonomous Region as the sample, collected data from 2010 to 2018, and analyzed it based on the coupling coordination theory. Findings: The results revealed that the comprehensive development evaluation index of the cultural industry and the tourism industry basically showed a year-on-year upward trend, and the development speed of the cultural industry is slightly higher than that of the tourism industry; the coupling degree of the regional cultural industry and tourism industry was at a high level; the coordination degree of the two industries increased gradually from 0.3971 in 2010 to 0.9425 in 2018. It indicated that the coupling development of the two industries continues to improve. However, the development speed of tourism industry slightly was slower than the development speed of the cultural industry. Improvements: This study attempts to develop an index to evaluate the tourism and cultural industries in an ethnic minority region and assess the coupling and coordination degree through an empirical analysis. This study emphasizes the need to better understand the integration of the cultural industry and the tourism industry as a process to complement each other, which can produce a positive synergy effect to benefit both the economy and the environment. This paper also provides development suggestions for the culture and tourism industry stakeholders in other areas of the world from the perspective of open innovation.
Keywords: 650; open innovation; coupling coordination; minority areas; the cultural industry; the tourism industry